Pengembangan Modul Pembelajaran Menulis Teks Eksposisi Untuk Siswa Kelas X Di SMA PM 1 Palembang - Octarina, Ayu (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to develop a learning module for writing exposition texts for grade X students at SMA PM 1 Palembang, in order to meet the needs of students and teachers and improve students' understanding and writing skills. This research uses the Research and Development (R&D) method that follows the steps developed by Jolly and Bolitho and Dick, Carey, and Carey. The first stage was the identification of students' and teachers' needs through questionnaires and interviews. The results show that students need a module that presents material on writing exposition texts in a complete, in-depth, and easy-to-understand manner, with an attractive and systematic display. Next, the module was developed by paying attention to the aspects of content, language, presentation, and graphics. The module was validated by four experts, whose results showed that the module was feasible to use with a total score of 78 or 86.67% of the maximum score. The limited trial showed that the use of this module was effective in improving students' writing ability, with an increase in the average score on the test before and after the use of the module. In conclusion, the developed module can be an effective solution in learning to write exposition texts at SMA PM 1 Palembang. Translated with DeepL.com (free version).